PENERIMAAN DIRI TUNA DAKSA BINAAN FORUM BANGUN ACEH MENGGUNAKAN ANALISIS ADLERIAN COUNSELING - Dara Maisun; C Casmini; Nurus Sa'adah (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2022)
This paper is motivated by observational data which shows that there are the physically disabled person who have a very high sense of low self-esteem even though they have been given counseling by the Forum Bangun Aceh. The causes of the unsuccessful counseling process can be analyzed using Adlerian Counseling. The process of good self-acceptance can be seen in the individual's ability when adapting to the environment so that it can provide a sense of self-satisfaction. If the environment rejects its presence, the individual will experience a setback and increase a sense of inferiority. Therefore, this writing aims: (1) toanalyze the process of self-acceptance of the physically disabled person by the Forum Bangun Aceh; (2) to analyze what factors are behind the success and failure of the counseling process for the disabled assisted by the Forum Bangun Aceh; and (3) to analyze the implications or impacts of the Adlerian Counseling analysis on the physically disabled person fostered by the Forum Bangun Aceh.The writing uses qualitative methods, interviews and observations. The results of this paper indicate Forum Bangun Aceh can be a facilitator to that physically disabled can develop their potential. The development of physically disabled self is hampered because they have low self-esteem, are not sure of themselves and feel doubt that their abilities will be accepted in a socoal environment. In the prosess of self-acceptance, the physically disabled should be with themselves as a disability and change the attitude of inferiority to superiority. The low self-esteem described in Adler’s theory is a psychological obstacle that usually occurs since puberty for various reasons and conditions. Self-acceptance for people with disabilities is very important in facing the reality of their own condition by minimizing a sense of inferiority to generate a sense of optimism, enthusiasm, self-understanding, and belief in their potential to move forward in carrying out their lives.